Macfarlane, B. Freedom to Learn: The Threat to Student Academic Freedom and Why it Needs to be Reclaimed - Nsibande, Rejoice (Critical Studies in Teaching and Learning, 2023)
This is a review of Macfarlane, B. 2017. Freedom to Learn: The Threat to Student Academic Freedom and Why it Needs to be Reclaimed. London: Routledge Taylor and Francis.